Angiomatosis of breast - an extremely rare benign vascular lesion of the breast: a case report - Krishna, Lanka; Sunetri, Padma; Ramana, Podili Venkata; Kumar, Shravan (International Surgery Journal, 2016)
Angiomatosis of the breast extremely rare benign vascular tumor. Very few cases reported in the literature. Complete excision and examination is required for the diagnosis of any benign vascular lesion in the breast. If the diagnosis of a benign vascular lesion is made on a partial excision, it must be stated to be contingent upon complete excision. These tumors are prone to local recurrence. Complete excision or simple mastectomy is the treatment of choice.